Design and baseline characteristics of the Short bouTs of Exercise for Preschoolers (STEP) study - Alhassan Sofiya; Nwaokelemeh Ogechi; Mendoza Albert; Shitole Sanyog; Whitt-Glover Melicia C; Yancey Antronette K (BMC, 2012)
Abstract Background Most preschool centers provide two 30-min sessions of gross-motor/outdoor playtime per preschool day. Within this time frame, children accumulate most of their activity within the first 10 min. This paper describes the design and baseline participant characteristics of the Short bouTs of Exercise for Preschoolers (STEP) study. The STEP study is a cluster randomized controlled study designed to examine the effects of short bouts of structured physical activity (SBS-PA) implemented within the classroom setting as part of designated gross-motor playtime on during-school physical activity (PA) in preschoolers. Methods/Design Ten preschool centers serving low-income families were randomized into SBS-PA versus unstructured PA (UPA). SBS-PA schools were asked to implement age-appropriate 10 min structured PA routines within the classroom setting, twice daily, followed by 20 min of usual unstructured playtime. UPA intervention consisted of 30 min of supervised unstructured free playtime twice daily. Interventions were implemented during the morning and afternoon designated gross-motor playtime for 30 min/session, five days/week for six months. Outcome measures were between group difference in during-preschool PA (accelerometers and direct observation) over six-months. Ten preschool centers, representing 34 classrooms and 315 children, enrolled in the study. The average age and BMI percentile for the participants was 4.1 ± 0.8 years and 69th percentile, respectively. Participants spent 74% and 6% of their preschool day engaged in sedentary and MVPA, respectively. Discussion Results from the STEP intervention could provide evidence that a PA policy that exposes preschoolers to shorter bouts of structured PA throughout the preschool day could potentially increase preschoolers' PA levels. Trial registration Clinicaltrials.gov, NCT01588392